Comparative Analysis of Toxic Responses of Organic Extracts from Diesel and Selected Alternative Fuels Engine Emissions in Human Lung BEAS-2B Cells - Libalova, Helena; Rossner, Pavel; Vrbova, Kristyna; Brzicova, Tana; Sikorova, Jitka; Vojtisek-Lom, Michal; Beranek, Vit; Klema, Jiri; Ciganek, Miroslav; Neca, Jiri; Pencikova, Katerina; Machala, Miroslav; et al. (International journal of molecular sciences, 2016)
This study used toxicogenomics to identify the complex biological response of human lung BEAS-2B cells treated with organic components of particulate matter in the exhaust of a diesel engine. First, we characterized particles from standard diesel (B0), biodiesel (methylesters of rapeseed oil) in its neat form (B100) and 30% by volume blend with diesel fuel (B30), and neat hydrotreated vegetable oil (NEXBTL100). The concentration of polycyclic aromatic hydrocarbons (PAHs) and their derivatives in organic extracts was the lowest for NEXBTL100 and higher for biodiesel. We further analyzed global gene expression changes in BEAS-2B cells following 4 h and 24 h treatment with extracts. The concentrations of 50 µg extract/mL induced a similar molecular response. The common processes induced after 4 h treatment included antioxidant defense, metabolism of xenobiotics and lipids, suppression of pro-apoptotic stimuli, or induction of plasminogen activating cascade; 24 h treatment affected fewer processes, particularly those involved in detoxification of xenobiotics, including PAHs. The majority of distinctively deregulated genes detected after both 4 h and 24 h treatment were induced by NEXBTL100; the deregulated genes included, e.g., those involved in antioxidant defense and cell cycle regulation and proliferation. B100 extract, with the highest PAH concentrations, additionally affected several cell cycle regulatory genes and p38 signaling.
Keywords: organic extracts; Cell Line, Transformed; transformované buněčné linie; Plant Oils; bronchy; biopaliva; gene expression profiles; epitelové buňky; Particulate Matter; pevné částice; Biofuels; anotace sekvence; Epithelial Cells; signální transdukce; Vehicle Emissions; diesel exhaust particles; stanovení celkové genové exprese; Plant Proteins; Signal Transduction; regulace genové exprese u rostlin; polycyklické aromatické uhlovodíky; látky znečišťující vzduch; Gene Expression Profiling; benzin; lidé; Gene Expression Regulation, Plant; Humans; alternative fuels; Molecular Sequence Annotation; Gasoline; výfukové emise vozidel; oleje rostlin; diesel; Bronchi; Polycyclic Aromatic Hydrocarbons; rostlinné proteiny; Air Pollutants